2012
DOI: 10.1080/0969160x.2012.718900
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to Accounting: Australian Indigenous Students' Experience

Abstract: Australian Indigenous people are under-represented in accounting studies and in the accounting profession. As part of an investigation of the cause of this situation such that it can be overcome, this project addresses the relevant study choices of high-school students in Darwin. Through semi-structured interviews with students and teachers, it is found that diverse cultural issues have significant impact on Indigenous students' study options and study success, that there are important differences between urba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…These include the under-representation of students in year 12 studies and the role of teachers in guiding and advising students toward careers and opportunities as a result of education in business studies (Lombardi & Clayton, 2006;Rkein & Norris, 2012). Business subjects may also be shunned because they are predominantly numeracy-based and support from teachers may be lacking if they believe their students do not have the necessary math level required in courses such as accountancy and finance.…”
Section: Barriers To Participation In Business Educationmentioning
confidence: 99%
See 4 more Smart Citations
“…These include the under-representation of students in year 12 studies and the role of teachers in guiding and advising students toward careers and opportunities as a result of education in business studies (Lombardi & Clayton, 2006;Rkein & Norris, 2012). Business subjects may also be shunned because they are predominantly numeracy-based and support from teachers may be lacking if they believe their students do not have the necessary math level required in courses such as accountancy and finance.…”
Section: Barriers To Participation In Business Educationmentioning
confidence: 99%
“…Indigenous knowledge and the teaching of cultural studies have been found to be excluded or marginalised in the curriculum (Barney, 2013;Rahman, 2013) by Western knowledge systems. Likewise sociocultural values clash in terms of teaching styles, pedagogies and course content (Pechenkina et al, 2011;Rkein & Norris, 2012). This clash can present as an insurmountable barrier when Indigenous students have to "acquire [Western] school cultural knowledge and succeed in education, at the expense of their cultural identity, practices and world views" (Rahman, 2013, p. 664).…”
Section: Barriers To Participation In Higher Educationmentioning
confidence: 99%
See 3 more Smart Citations